Vertical accuracy assessment of various open-source DEM data: DEMNAS, SRTM-1, and ASTER GDEM - Susetyo, Danang Budi (Geodesy and Cartography, 2023)
DEM can be used optimally when it has good accuracy. Thus, assessing DEM data quality is mandatory before use it for specific thematic applications. Recently, there are open-source DEM data that can be downloaded and used freely by users, such as SRTM and ASTER GDEM. However, Indonesia tried to develop their own national seamless DEM, called DEMNAS. This study aims to evaluate the open-source DEMs that are popular in Indonesia: DEMNAS, SRTM-1, and ASTER GDEM. Accuracy assessment was conducted by comparing the DEMs to GPS measurements. The results showed that SRTM-1 had the best accuracy with 5.529 meters, followed by DEMNAS and ASTER GDEM with 8.172 meters and 13.632 meters, respectively. We also analyzed the linear relation between DEMs and GPS elevation data using the coefficient of determination, and all DEMs showed good R2 values. Lastly, the correlation between the error and the height of DEMs was also examined. The results were SRTM-1 had correlation between the height and accuracy, as well as ASTER GDEM. In contrast, the errors in DEMNAS were relatively uniform in all range of elevation.